Crustal structure of southeast Australia from teleseismic receiver functions - M. Bello; M. Bello; D. G. Cornwell; N. Rawlinson; A. M. Reading; O. K. Likkason (Solid Earth, 2021)
In an effort to improve our understanding of the seismic character of the crust beneath southeast Australia and how it relates to the tectonic evolution of the region, we analyse teleseismic earthquakes recorded by 24 temporary and 8 permanent broadband stations using the receiver function method. Due to the proximity of the temporary stations to Bass Strait, only 13 of these stations yielded usable receiver functions, whereas seven permanent stations produced receiver functions for subsequent analysis. Crustal thickness, bulk seismic velocity properties, and internal crustal structure of the southern Tasmanides – an assemblage of Palaeozoic accretionary orogens that occupy eastern Australia – are constrained by H–κ stacking and receiver function inversion, which point to the following: a ∼ 39.0 km thick crust; an intermediate–high Vp/Vs<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="28pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="bfd54d15381023f9a454fbbd52948b7b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-12-463-2021-ie00001.svg" width="28pt" height="16pt" src="se-12-463-2021-ie00001.png"/></svg:svg> ratio (∼ 1.70–1.76), relative to ak135; and a broad (> 10 km) crust–mantle transition beneath the Lachlan Fold Belt. These results are interpreted to represent magmatic underplating of mafic materials at the base of the crust. a complex crustal structure beneath VanDieland, a putative Precambrian continental fragment embedded in the southernmost Tasmanides, that features strong variability in the crustal thickness (23–37 km) and Vp/Vs<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="28pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="87a30c690410d7a09a7056c68eebd7c3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-12-463-2021-ie00002.svg" width="28pt" height="16pt" src="se-12-463-2021-ie00002.png"/></svg:svg> ratio (1.65–193), the latter of which likely represents compositional variability and the presence of melt. The complex origins of VanDieland, which comprises multiple continental ribbons, coupled with recent failed rifting and intraplate volcanism, likely contributes to these observations. stations located in the East Tasmania Terrane and eastern Bass Strait (ETT + EB) collectively indicate a crust of uniform thickness (31–32 km), which clearly distinguishes it from VanDieland to the west. Moho depths are also compared with the continent-wide AusMoho model in southeast Australia and are shown to be largely consistent, except in regions where AusMoho has few constraints (e.g. Flinders Island). A joint interpretation of the new results with ambient noise, teleseismic tomography, and teleseismic shear wave splitting anisotropy helps provide new insight into the way that the crust has been shaped by recent events, including failed rifting during the break-up of Australia and Antarctica and recent intraplate volcanism.